Kendala Pelaksanaan Regulasi tentang Pembantu Rumah Tangga (PRT) di Yogyakarta - Muryanti Muryanti; Ekawati Sri Wahyuni; Rilus Kinseng; Aida Vitayala S.Hubeis (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Non-Governmental Organizations (NGO), through their advocacy program, have succeeded in protecting the housemaids and their employers, both at provincial as well as national levels. Some regulations on this issue have been issued as results of their advocacy program include: SuratEdaranGubernur DIY Tahun 2003 (Governor of Yogyakartas Handbill 2003), Peraturan Gubernur DIY No. 48 Tahun 2010 (Governor of Yogyakartas Bylaw 2010), Peraturan Walikota Yogyakarta No. 31 Tahun 2011, (Mayor of Yogyakarta Citys Bylaw 2011), and Peraturan Menteri Ketenagakerjaan RI No.2 Tahun 2015 (Ministry of Labors Law No.2/2015). This paper discusses some difficulties in implementing those regulations, especially related to the debatable content, such as: the definition of Pembantu Rumah Tangga/PRT (Housemaids), whether they are considered as helpers or labor; deciding their working hours; having a written or oral contract; and involving the third parties in the relationship between housemaids and their employers. Some reasons are found in explaining those difficulties: in any situation, PRT (housemaids) are considered as an informal work; there is a strong notion of familial relationship, where emotional relation is preferred than formal relationship. One thing that should be noted related to the importance of legal protection for housemaids is the need of continuous advocacy in dealing with managing their relationships with others, especially employers and the third parties. Keywords: PRT (housemaid), Employer, Regulations, Formal and Familial Relationship